Reproductive Aging and Hepatic Fibrosis Progression in Human Immunodeficiency Virus/Hepatitis C Virus–Coinfected Women - Sarkar, Monika (Clin Infect Dis, 2017)
BACKGROUND: Severity of hepatic fibrosis is greater in postmenopausal than in premenopausal women, perhaps owing to protective effects of estrogens. However, prior studies of estrogen and liver fibrosis lack serial fibrosis measures, adjustment for age, or longitudinal observations in coinfected populations. METHODS: In a longitudinal cohort of women coinfected with human immunodeficiency virus (HIV) and hepatitis C virus (HCV), we assessed fibrosis progression across reproductive age, using validated serum fibrosis markers, aminotransferase platelet ratio index (APRI) and fibrosis 4 (FIB-4). Fibrosis rate was evaluated within each woman as she transitioned from pre- to postmenopause, defined by a biomarker of ovarian function. RESULTS: The median follow-up (n = 405) was 9.1 years (interquartile range, 5.0–15.2 years), with a median menopausal age of 49 years (47–52 years). When fully controlled for chronologic aging, the fibrosis progression rate was accelerated during perimenopause, as shown using FIB-4 (0.12 units per year faster than during premenopause; 95% confidence interval [CI], .02–.21; P = .01) and APRI (0.05 units per year faster; −.002 to .09; P = .06). Accelerated fibrosis was also observed during postmenopause compared with premenopause, for FIB-4 (0.14 units per year faster; 95% CI, −.01 to .29; P = .07) and APRI (0.07 units per year faster; −.003 to .15; P = .06). Accelerated fibrosis in perimenopause persisted after adjustment for Hispanic ethnicity, antiretroviral use, and alcohol (0.10 FIB-4 units per year faster than during premenopause; 95% CI, .008–.20; P = .03). CONCLUSIONS: In HIV/HCV-coinfected women, hepatic fibrosis accelerates with reproductive aging. Accelerated fibrosis begins in perimenopause, highlighting a previously unrecognized group of women at increased risk for advanced fibrosis and associated complications. Longitudinal analyses of fibrosis rates across reproductive age should be conducted in non–HCV-related liver diseases, given potential implications in a broader spectrum of women.